Do 16 i starshe . Do 16 i starshe . Under 16 and Over . До 16 и старше - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Training in vocational schools; the Museum of the Soldiers-Internationalists and the activities of its members; clubs for children and teenagers; a story about a students from the Suvorov Military School; interviews with young musicians and poets; segment on ceramic artists in Ukraine. Series description: TV program of the First channel of Russia and the USSR, dedicated to the problems of young people. The program dealt with the current problems of youth life: homelessness, the movement of "rockers," drug addiction, the problem of "bullying," leisure, and family relations. Обучение в ПТУ; деятельность членов Музея воинов-интернационалистов; кружки для детей и подростков; о курсанте Суворовского училища; интервью с юными музыкантами и поэтами; мастера керамики на Украине. Описание серии: Телевизионная программа Первого канала СССР и России, посвящённая молодёжи. Программа освещала актуальные проблемы молодежной жизни: беспризорность, движение "рокеров," темы наркомании и "дедовщины," проблемы досуга и взаимоотношений в семье.